2020
DOI: 10.1063/1.5123451
|View full text |Cite
|
Sign up to set email alerts
|

Shaping effects on scrape-off layer plasma turbulence: A rigorous validation of three-dimensional simulations against TCV measurements

Abstract: The effect of plasma shaping on scrape-off layer (SOL) plasma turbulence is investigated through a rigorous validation exercise. Two-and three-dimensional simulations of the SOL plasma dynamics in three TCV limited discharges are carried out with the GBS code. These discharges realize an almost circular magnetic equilibrium, an elongated equilibrium, and an elongated equilibrium with negative triangularity. For the three plasma discharges, three simulations are performed, considering (i) a three-dimensional mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
5
15
0
Order By: Relevance
“…In particular, our theoretical scaling law does not include the effect of plasma triangularity, which has been studied with GBS in Refs. [73,74] for a limited configuration, showing that the near SOL width is enhanced (reduced) by positive (negative) values of triangularity, in agreement with experimental observations [75]. In addition, interchange-like turbulence, which can develop along the divertor leg, can increase the power fall-off length at the target plate [76].…”
Section: Near Solsupporting
confidence: 81%
“…In particular, our theoretical scaling law does not include the effect of plasma triangularity, which has been studied with GBS in Refs. [73,74] for a limited configuration, showing that the near SOL width is enhanced (reduced) by positive (negative) values of triangularity, in agreement with experimental observations [75]. In addition, interchange-like turbulence, which can develop along the divertor leg, can increase the power fall-off length at the target plate [76].…”
Section: Near Solsupporting
confidence: 81%
“…However, the quality of the validation is very high, with values of Q = 18.6 − 19.4, reflecting the large number of observables used in the validation. The results of the quantitative analysis correspond to a lower level of agreement and a significantly higher quality compared to previous works using the same methodology, such as Ricci et al, 2015 [24], which found a χ = 0.5 − 0.75 with a Q ≈ 4 for TORPEX plasmas and Riva et al, 2020 [16] which found a value of χ = 0.45 and Q ≈ 4 for limited TCV discharges. We note that a companion work to this paper, published as Galassi et al, 2021 [25] found χ = 0.85−1.0 and Q ≈ 4 in TORPEX plasmas with an internal X-point.…”
Section: Quantitative Validation and Sensitivity Analysissupporting
confidence: 45%
“…Direct numerical turbulence simulations require more sophisticated physical models than transport codes, and orders-of-magnitude more computational resources due to the 3D multi-scale nature of turbulence. Nevertheless, advances in numerical methods and larger, faster supercomputers mean that full-size † turbulence simulations of the boundary region of existing experimental devices like COMPASS [12]- [14], MAST [15], TCV [16], Alcator C-mod [17]- [19], AUG [20] and DIII-D [17] are now achievable, allowing direct comparison between turbulence simulations and experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, however, in order to develop full predictive capabilities, these codes need to undergo a thorough validation with experimental data. Initially, validation exercises focused on simple magnetic configurations [22,23], while more recently they have been extended to larger experiments, as TCV (Tokamak Ă  Configuration Variable [24]), in limiter configuration [25]. Multi-code validations of seeded blobs had been performed against TORPEX [26] and MAST [27] experiments.…”
Section: Introductionmentioning
confidence: 99%